3D printing of phase change hydrogels - Hossain, Md Alal; Ahmed, Shajuyan; Hossain, Md Sabir; Hossain, Khan Rajib (Vietnam Journal of Science and Technology, 2026)
Phase change materials (PCM) can change from solid to liquid at a constant temperature, allowing them to retain more heat than other materials. 3D printing of PCM with hydrogels opens up new manufacturing possibilities by increasing productivity and functional diversity. This article reviews recent advances in phase change hydrogel 3D printing, focusing on metal-infused hydrogels, graphene-based, bio-based PCM, and chitosan-based materials. In particular, a new 3D printing method was developed, in which rheology was modulated using carbomers to produce a variety of functional hydrogels, including magnetic, dual-network, thermosensitive, and other types. Highly loaded PCM/cellulose nanofiber (CNF) ink and phase change organic hydrogel (PCOH) are new options for such encapsulation and thermal stability. This article discusses how hydrogels resemble the extracellular matrix and can be used in bioprinting to support basic biological processes. Despite all the progress, more research is needed to address issues such as the flexibility of PCM and achieving high energy storage density. This review article highlights how hydrogels and 3D printing can have a revolutionary impact. Future directions and potential applications in the field of flexible electronics, responsive drug delivery systems, and tissue engineering are covered in this article.